Variants at the 9p21 locus and melanoma risk - Maccioni, Livia; Rachakonda, P. Sivaramakrishna; Lorenzo Bermejo, Justo; Planelles, Dolores; Requena, Celia; Hemminki, Kari; Nagore, Eduardo; Kumar, Rajiv (BMC cancer, 2013)
The influence of variants at the 9p21 locus on melanoma risk has been reported through investigation of CDKN2A variants through candidate gene approach as well as by genome wide association studies (GWAS).